A report on Gummosis of some trees in Telangana - Sushama, P R; Vijjulatha, M; Manoharachary, C; Sana, Hajera; Yasmeen, Mehtab (Indian Journal of Plant Protection, 2025)
During December to February, 2025 in many locations in Telangana state neem trees showed natural oozing of gum like substances from their stems. The phenomenon is called “Gummosis” and it may be due to different factors like parasitic invasion, microbial infection, chemical stress, physical injury or climate change. This is the first report on the occurrence of gum exudation in neem trees along with many other trees from different families like Moraceae, Fabaceae, Mimosaceae etc. Among all the families, Meliaceae family was found to profusely exude gum while other trees also showed significant exudation. There was a synchronous gummosis of trees of different families producing gum from their bark naturally at different places of Telangana indicating symptoms of physiological stress. Owing to the importance of trees as they are unmatched providers and protectors, utmost care has to be taken in aiding their protection. The main aim of the present research work was to find the solution to safeguard the trees as they are natural wealth and most importantly bio-wealth with multifarious properties for sustainable future.